Biodegradation of a polylactic acid/polyvinyl chloride blend in soil - Santana, V. T. [UNESP]; Goncalves, S. P. C. [UNESP]; Agnelli, J. A. M.; Martins-Franchetti, S. M. [UNESP] (Wiley-Blackwell, 2012)
This study investigated the microbial action in soil on poly(L-lactic acid) (PLLA) and polyvinyl chloride (PVC) films and a PLLA/PVC 7 : 3 blend, using Fourier transform infrared spectroscopy (FTIR), contact angle and scanning electron microscopy (SEM). The films (50 mu m) were obtained from the evaporation of dichloromethane solutions and buried in soil columns, in controlled conditions, for 120 days. The results showed that the surface of the PLLA films and blend became 18 and 31% more hydrophilic, respectively. The morphology of the films also changed after 120 days of microbial treatment, particularly that of the PLLA phase in the blend, confirmed by structural and conformational changes in the FTIR CO region at 12001000 cm1 and an increase in the relative intensity of the band at 1773 cm1, which was attributed to C O group vibration due to a rotational isomer in the interlamellar region (semi-ordered region). Besides the biotreated PVC presented changes in the C-Cl band at 738 cm1, due to the presence of some PVC conformational isomer. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: PLLA; PVC; FTIR; biodeterioration; contact angle